CD4 T cell counts are inversely correlated with anti-gp120 cluster A antibodies in antiretroviral therapy-treated PLWHResearch in context - Mehdi Benlarbi; Jonathan Richard; Tommaso Clemente; Catherine Bourassa; William D. Tolbert; Suneetha Gottumukkala; Marc Messier-Peet; Halima Medjahed; Marzena Pazgier; Frank Maldarelli; Antonella Castagna; Madeleine Durand; et al. (EBioMedicine)
Summary: Background: While antiretroviral therapy (ART) efficiently suppresses viral replication, inflammation and immune dysfunction persist in some people living with HIV-1 (PLWH). HIV-1 soluble gp120 (sgp120) has been detected in PLWH plasma and its presence is linked to immune dysfunction. It was reported that sgp120 binding to CD4 on uninfected bystander CD4+ T cells sensitises them to cellular death via antibody-dependent cellular cytotoxicity (ADCC) mediated by non-neutralising anti-cluster A antibodies (Abs) present in PLWH plasma. Methods: We included plasma from 520 PLWH on ART from three independent cohorts for measurements of anti-cluster A Abs and anti-CD4 binding site (anti-CD4BS) Abs. Associations between CD4+ T cell counts and anti-cluster A Abs was assessed using generalised least squares linear regression models, adjusting for potential confounders including age, sex, nadir CD4 and duration of ART. The role of anti-CD4BS Abs was evaluated using flow-cytometry based ADCC assays with primary CD4+ T cells. Findings: We observed that non-neutralising anti-cluster A Abs are negatively associated with CD4+ T cell counts. Anti-CD4BS antibodies blocked the coating of uninfected bystander cells by sgp120, thereby preventing their elimination by ADCC. Supporting a protective role of anti-CD4BS antibodies, their presence in PLWH plasma abrogated the negative association between CD4 counts and anti-cluster A Abs. Interpretation: Our results reveal that anti-cluster A Abs are associated with immune dysfunction in PLWH and anti-CD4BS antibodies might have a beneficial impact in these individuals. Funding: This study was supported by the Canadian Institutes of Health Research, the Canada Foundation for Innovation, the Fonds de Recherche du Québec-Santé, and the National Institutes of Health.